Minimizing Cigarette Smoke Exposure Based on IoT Using Automatic Filtration and MQ-2 Sensor - Sinuraya, M.Fahriza; Sinuraya, M. Fahriza; Irvan, Irvan (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
This study designs and implements an Internet of Things (IoT)-based system to minimize cigarette smoke exposure in enclosed spaces. The system uses an MQ-2 sensor integrated with an ESP32 microcontroller, along with automatic fan-based filtration and a HEPA + activated carbon filter. The method used is research and development (R&D) through the design, implementation, testing, and analysis stages. The results show that the MQ-2 sensor is able to detect cigarette smoke concentrations in real time and transmit data to the Thinger.io platform. An LED traffic light indicator system is used to show air quality status, while an automatic relay controls the fan to speed up the filtration process. The trial showed that the system was able to reduce cigarette smoke levels by more than 70% and provide warning notifications to users. Thus, this system has the potential to increase awareness of active smokers and protect passive smokers in the household environment.